Principal competency model development: Phenomenological design with coaching techniques in Sekolah Penggerak - Muhamad Galang Isnawan; Sudirman Sudirman (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2022)
Sekolah Penggerak is one of the best episodes of the many Merdeka Belajar episodes. A separate curriculum known as Kurikulum Merdeka was prepared to support the program. The change in the principal’s competency model then became one of the unique phenomena in the curriculum change. The facts reveal that school principals cannot adapt quickly to this phenomenon, so this study aims to help school principals adapt more quickly to changes in competency models with coaching techniques. This study uses a phenomenological design because it wants to know the experiences that principals experience regarding the use of coaching techniques in responding to the phenomenon of changing competency models. The participants were three principals (51-55 years old) with 2-5 years of experience as principals. The instruments used are coaching questions developed in Sekolah Penggerak. Data is collected online through Google Meet and analyzed using qualitative data analysis techniques. The study results then revealed that coaching techniques could to assist school principals in developing a model of school leadership competence, especially self-development and other people’s development, as well as learning leadership. This study also hopes that the principal will actively involve parents or guardians of students as mentors and learning resources.